Peramalan Jumlah Wisatawan Nusantara di Kota Tomohon Menggunakan Regresi Linear - Siwi, Vena Diane; Polii, Michelle; Tambayong, Fresa; Wowiling, Abel; Kelen, Divaria; Bungangu, Pricillya; Hamid, Hizkia; Mangobi, James U. L.; Maukar, Marvel (LPPM Politeknik Saint Paul Sorong, 2025)
Tourism is a strategic sector that has an important role in promoting regional economic growth through increased local revenue and job creation. The province of North Sulawesi, especially the city of Tomohon, has superior tourism potential in the form of natural beauty and cultural wealth which is the main attraction for Indonesian tourists. Historical Data show a trend towards an increase in the number of tourist visits from 2015 to 2024, despite a significant decrease in 2020 due to the COVID-19 pandemic. This study aims to predict the number of tourists visiting the city of Tomohon archipelago using simple linear regression. Based on the results of the analysis, the regression equation y = 276,756 + 23,468 X was obtained, which showed that the number of tourists increased on average by 23,468 people per year. Using this model, the prediction of the number of Indonesian tourists visiting Tomohon City in 2025 is around 534,904 people. The results of this forecasting are expected to provide useful information for the development of sustainable and competitive tourism.